Learning in Practice: An Ethnographic Exploration of the Meaning of Learning at a Maritime Training Institute (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This study aims to understand the classroom pedagogy followed in an elite, reputed maritime academy in India and the lives of cadets undergoing training there. Data is drawn from an ethnographic engagement of the researchers (authors) with the cadets intheir life-world inside the academy which facilitated a firsthand exploration of the cadet life, generating valuable insights about their daily routine, social interaction and academic life. Employing focus-group discussions, classroom observation and pre-testand post-test methodologies, the study revealed the demanding nature of cadet-life emergent from rigorous training practices, strict discipline and exposure to challenging tasks which come from diverse instructional methods which instructors adopt. The studyindicates that the pedagogic instructions emphasise on building essential maritime skills and knowledge through practical demonstrations and simulations exercises following the situatedness of cognition around the tasks. The study further unpacks a deeper understanding of the challenges of practice and meaning making processes within apractice as faced by cadets which enable development of support systems and interventions to enhance their well-being and success during maritime training.